Two genes, ANS and UFGT2, from Vaccinium spp. are key steps for modulating anthocyanin production - Nguyen, Han M.; Putterill, Joanna; Dare, Andrew P.; Plunkett, Blue J.; Cooney, Janine; Peng, Yongyan; Souleyre, Edwige J. F.; Albert, Nick W.; Espley, Richard V.; Günther, Catrin S. (Frontiers in Plant Science, 2023)
Anthocyanins are a major group of red to blue spectrum plant pigments with many consumer health benefits. Anthocyanins are derived from the flavonoid pathway and diversified by glycosylation and methylation, involving the concerted action of specific enzymes. Blueberry and bilberry (Vaccinium spp.) are regarded as ‘superfruits’ owing to their high content of flavonoids, especially anthocyanins. While ripening-related anthocyanin production in bilberry (V. myrtillus) and blueberry (V. corymbosum) is regulated by the transcriptional activator MYBA1, the role of specific structural genes in determining the concentration and composition of anthocyanins has not been functionally elucidated. We isolated three candidate genes, CHALCONE SYNTHASE (VmCHS1), ANTHOCYANIDIN SYNTHASE (VmANS) and UDP-GLUCOSE:FLAVONOID-3-O-GLYCOSYLTRANSFERASE (VcUFGT2), from Vaccinium, which were predominantly expressed in pigmented fruit skin tissue and showed high homology between bilberry and blueberry. Agrobacterium-mediated transient expression of Nicotiana benthamiana showed that overexpression of VcMYBA1 in combination with VmANS significantly increased anthocyanin concentration (3-fold) Overexpression of VcUFGT2 modulated anthocyanin composition, while VmCHS1 showed no effect above that induced by VcMYBA1. In strawberry (Fragaria × ananassa), combined transient overexpression of VcUFGT2 with a FLAVONOID 3´,5´-HYDROXYLASE from kiwifruit (Actinidia melanandra) modulated the anthocyanin profile to resemble the glycosylation patterns that can be seen in blueberry and bilberry with regard to galactosides and arabinosides. These findings provide insight into the role of the final steps of biosynthesis in modulating anthocyanin production in Vaccinium and may contribute to the targeted breeding of new cultivars with improved nutritional properties.